Editorial notes for the ESPR special issue on Green Technology and Industrial Revolution 4.0 for a greener future - Low, Siew Chun; Vo, Dai‑Viet N.; Hameed, Bassim H.; Sunarti, Abd Rahman (Springer, 2023)
As the world faces unprecedented environmental challenges, it is increasingly clear that green technology is one of the most effective ways to protect our planet’s natural resources and address pressing environmental problems. Furthermore, the integration of sustainability with Industry Revolution 4.0 has the potential to revolutionize the entire environmental and chemical engineering industry. The theme of this special issue highlights the need to embed green technology and Industry 4.0 into sustainable development goals, with a particular emphasis on meeting the needs of the bottom billions in the community. Articles published in this issue offer valuable insights into how green technology can be harnessed to promote sustainable development, and how Industry 4.0 can be leveraged to drive innovation and change.